Apixaban Level and Its Influence on Immunosuppression and Graft Outcome in Kidney Transplant Recipients With Atrial Fibrillation. Issue 5 (October 2021) - Green, Hefziba; Rahamimov, Ruth; Spectre, Galia; Rozen-Zvi, Benaya; Fuchs, Shmuel; Avni, Shiri; Nissan, Ran
Abstract : Background: Currently, there is limited information on the level of apixaban in kidney transplant (KT) patients with atrial fibrillation and the influence of apixaban therapy on the level of immunosuppression and graft function. Methods: This was a cross-sectional prospective study of 19 KT patients treated with apixaban. The levels of apixaban were measured using a chromogenic assay calibrated for apixaban and compared with those predicted by the manufacturer. Mean immunosuppression trough levels before and after apixaban treatment initiation were calculated using 3 consecutive measurements. Apixaban levels were compared with a historical control group comprising of 20 nontransplant patients with atrial fibrillation who were treated with the standard 5-mg bid apixaban dosage. Results: All KT patients should have been treated with the standard 5-mg bid apixaban dosage according to the clinical parameters; however, 7 were inappropriately treated with a reduced dosage (2.5-mg bid). There was no significant difference in apixaban level between KT patients treated with the 5-mg bid dosage and nontransplant patients. No KT patient administered the standard dose had out-of-range levels. Peak GM level was significantly lower in KT patients administered an inappropriately reduced dose ( P = 0.05). Two patients had below-range peak levels. Apixaban treatment initiation had minimal influence on the level of immunosuppression. Furthermore, it had no adverse impact on graft function. Conclusions: Similar to nontransplant patients, KT patients administered the standard 5-mg bid dosage had apixaban levels that were well within the recommended manufacturers' expected ranges. In addition, this dosage had minimal influence on immunosuppression and no effect on graft function.